JEAN WYLLYS -DO BBB AO AUTOEXÍLIO: DISCURSO, REPRESENTAÇÃO SOCIAL E LGBTQIA+FOBIA - Sessa, Ariel (2022)
In this PhD dissertation we analyse masses media news that reinforce the LGBTQIA+ group’s social representation as subaltern, which can result in social phobia, potentialized by intersectionality. Our corpus consists of 41pieces of news published in G1, from 2011 to 2019, in which there is a mention of the former federal deputy Jean Wyllys, both in the headlines or in the text. These pieces of news were selected by the search engine of the Globo group website, in which the macro propositions of the speech journalism are related to the LGBTQIA+ theme. We chose the social actor because he belongs to the LGBTQIA+ minority in an intersectionalized way and represents this group – as a public politician - through his agendas for the benefit of the group. Moreover, he was a federal deputy in the period of the analysed corpus, and the Globo group was chosen for having released him in the media. We believe that there is maintenance of heteronormative dominance in relation to LGBTQIA+ members from the general apprehension of the discourse through the deduction of conservative values that involves this minority theme. There is, therefore, the use of Jean Wyllys’ social representation as a minority referent, enhanced by the intersections that compose it, which promotes the perpetuation of an unequal social and LGBTQIA+phobic relationship. These apprehensions transcend the figure of the social actor and culminate in the entire LGBTQIA+ group. We chose the multidisciplinary theoretical framework found in Critical Discourse Studies, focused on the sociocognitive approach of van Dijk (1992a, 1992b, 2001, 2002, 2005a, 2005b, 2012, 2013, 2015a, 2015b, 2015c, 2016a, 2016b, 2016c, 2016c, 2017a, 2017b and 2018), in addition to issues related to the intersectionalities of gender, race and social class in Akotirene (2019), Cooper (2015), Crenshaw (1989, 2002), Deleuze and Guattari (2011), Hall (2006), Izharuddin (2010), Lanehart (2009), Louro (2008) and Ribeiro (2016); and the theory of Social Representation in Moscovici (2015) and apprehensions of face studies in Goffman (2004, 2014); both related to linguistic-discursive aspects. We selected the historical context of the social actor Jean Wyllys, and consider cultural issues linked to the history of LGBTQIA+ struggles in Brazil and around the world. From the analyses we confirm our hypothesis of the maintenance of the hegemonic power through the speeches produced in the published news by G1 when the journalistic direct speech moves away and exempts itself from its social responsibility. Also, we saw that when the journalist opts for linguistic-discursive choices linked to social prejudice and when the direct speech of the social actor is presented in isolation, the social imaginary that LGBTQIA+ issues are only of interest to members of this social group is reinforced.